2020
DOI: 10.1002/ijch.201900167
|View full text |Cite
|
Sign up to set email alerts
|

In Praise of Basic Research as a Vehicle to Practical Applications: Palladium‐Catalyzed Coupling to Form Carbon‐Nitrogen Bonds

Abstract: Two groups' research initiated to address two very different questions on problems of basic chemical research led, after much effort on catalyst development and studies of reaction mechanism, to the discovery and development of the coupling of amines with aryl halides in a practical fashion.[a] S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Regarding C−N coupling reactions, aryl amination via combined photoredox/nickel catalysis is a key discovery that attracted considerable attention (Figure 2 a), [20a] because this represents a complementary method to analogous palladium catalyzed reactions [36] . In particular, the reductive elimination step resulting in C−N bond formation was much in focus.…”
Section: Scope Of Light‐driven Nickel‐catalyzed Cross‐coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding C−N coupling reactions, aryl amination via combined photoredox/nickel catalysis is a key discovery that attracted considerable attention (Figure 2 a), [20a] because this represents a complementary method to analogous palladium catalyzed reactions [36] . In particular, the reductive elimination step resulting in C−N bond formation was much in focus.…”
Section: Scope Of Light‐driven Nickel‐catalyzed Cross‐coupling Reactionsmentioning
confidence: 99%
“…Regarding CÀNc oupling reactions, aryl amination via combined photoredox/nickel catalysis is ak ey discoveryt hat attracted considerable attention (Figure 2a), [20a] because thisr epresents ac omplementary method to analogous palladium catalyzed reactions. [36] In particular, the reductive elimination step resultingi nC ÀNb ond formation was much in focus. Partly based on early studies,w hich indicated that Ni II amido complexes tend to not undergo reductiveelimination at room temperature, [17] photo-driven oxidationo fN i II to Ni III wasc onsidered essential.…”
Section: Scope Of Light-driven Nickel-catalyzedc Ross-coupling Reactionsmentioning
confidence: 99%
“…The Buchwald–Hartwig amination is a chemical reaction used in organic chemistry for the synthesis of carbon–nitrogen bond-containing products. The reaction is a coupling of amines with arylhalides via a palladium catalyst. , This process has simplified the synthesis of pharmaceutical and agrochemical agents, among other relevant chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Palladium-catalyzed cross-coupling is one of the most powerful tools in modern synthetic chemistry, [1][2][3] with widespread application in total synthesis, 4 pharmaceutical discovery and process chemistry, [5][6][7] agrochemistry, 8 and materials synthesis. 9 Given the large number of reaction variables to optimize for every new system, there is a daunting variety of reported reaction conditions for each general transformation.…”
Section: Introductionmentioning
confidence: 99%